A Scoping Review on Fast Diagnosis of Tuberculosis: Counting Clinical Trials and Patent Highlights - Sahiba Parveen; Shahjad; Sisir Nandi (Reviews on Recent Clinical Trials, 2026)
Introduction: Tuberculosis (TB), induced by Mycobacterium tuberculosis (Mtb), constitutes a significant global public health issue, particularly for immunocompromised individuals who have HIV or cancer and are susceptible to latent tuberculosis. The Directly Observed Treatment Short (DOTS) course comprises isoniazid, rifampin, pyrazinamide, and ethambutol, which are administered to treat tuberculosis. Intentional or unintentional missed doses or inferior formulations have resulted in MDR-TB. Prompt and correct diagnosis is urgent to initiate treatment. The present study attempts to explore patient demographics, prompt TB diagnosis, and anti-tubercular medications under surveillance. Methods: A comprehensive literature search was performed to identify relevant studies published between 2018 and 2025, using electronic databases including PubMed, Scopus, Web of Science, ScienceDirect, and Google Scholar. Search terms were applied using combinations of controlled vocabulary and free-text keywords, including Mycobacterium tuberculosis, MDR and XDR-TB, antitubercular drugs, clinical trials, and patents on fast detection of tuberculosis and easy diagnosis of Mtb. Studies not focused on the said area were excluded. Results: Traditional diagnostic methods, while relatively affordable, were found to be timeconsuming and limited in sensitivity, particularly in HIV-positive TB patients to whom conventional immune-based tests may yield false-negative results. The present study reviewed novel diagnostic technologies, including advanced molecular techniques such as RT-qPCR and RNA sequencing, which offered rapid, highly specific identification of drug-resistant strains. Point-of-care platforms and immunological assays showed strong potential for deployment in resource-limited settings, addressing critical gaps in diagnostic access. Gene expression profiling further enabled distinguishing active TB from latent infection and predicting treatment response, providing a foundation for more personalized therapeutic strategies. Discussion: Rapid diagnosis of the specific disease can initiate appropriate treatment, which can save the patient's life. Conclusion: Timely and accurate diagnosis of TB, particularly drug-resistant forms, is essential for guiding appropriate treatment and preventing the further spread of MDR-TB and XDR-TB. Early TB detection helps make the right choice of specific current antitubercular chemotherapeutics, as strongly recommended in the present scoping review for the global effort to eradicate drug-resistant tuberculosis.